Symmetry- Adapted Formulation Of The Combined G-Particle-Hole Hypervirial Equation And Hermitian Operator Method - Alcoba, Diego Ricardo (2014)
High accuracy energies of low-lying excited states, in molecular systems,have been determined by means of a procedure which combines the G-particle-holehypervirial (GHV) equation method (Alcoba et al. in Int J Quantum Chem 109:3178,2009) and the Hermitian operator (HO) one (Bouten et al. in Nucl Phys A 202:127,1973). This work reports a suitable strategy to introduce the point group symmetrywithin the framework of the combined GHV-HO method, which leads to an improve-ment of the computational efficiency. The resulting symmetry-adapted formulation has been applied to illustrate the computer timings and the hardware requirements inselected chemical systems of several geometries. The new formulation is used to studythe low-lying excited states torsional potentials in the ethylene molecule.